Comparison of the measuring efficacy of transepidermal water loss of a reasonably priced, portable closed‐chamber system device H4500 with that of rather expensive, conventional devices such as Tewameter® and Vapometer®. Issue 4 (18th May 2017) - Kikuchi, K.; Asano, M.; Tagami, H.; Kato, M.; Aiba, S.
Abstract : Background/Purpose: Although measuring transepidermal water loss (TEWL) is important to assess the barrier function of the stratum corneum (SC), the commercially available instruments are rather expensive. Recently launched Model H4500 employs a closed‐chamber system to measure TEWL and is more reasonably priced compared to devices currently in general use. Methods: To check the reproducibility of the obtained data with H4500, we conducted measurements on the volar forearms of healthy volunteers and compared these data with those measured with Vapometer ® and Tewameter ® . Then, we checked the correlations between the TEWL data obtained with these different devices on the same volar forearms of 15 healthy volunteers before and after the artificial production of barrier damage of the SC by tape stripping or by 0.5% aqueous solution of sodium lauryl sulfate. Results: The obtained intra‐class correlation coefficient (ICC, [1, 1]) with 95% CI of H4500 was 0.927 (0.835‐0.978). Namely, an excellent correlation could be found in the values of TEWL measured with these three different instruments not only on healthy skin but also on the artificially barrier‐damaged skin. Conclusions: H4500 is considered to be practical for daily use because of its performance as well as its reasonable price as compared with conventional devices.